The Impact of University Academicians as Solution Providers: A Case Study of SDG-Oriented Community- Based Projects in Kelantan and Terengganu - Azlizan Talib,; Khaled, Norhana; Hasan, Muhammad Rahimi; Othman, Norfatiha; Nik Hasif, (Journal of Technical Education and Training, 2025)
This article examines the role of university academicians as solution providers in community farming initiatives under the All-Party Parliamentary Group Malaysia on Sustainable Development Goals (APPGM-SDG). It focuses on the impact of their participation in beneficiary self-development in selected projects within the Terengganu and Kelantan constituencies in the Eastern Region. This paper adopts a fully qualitative approach, utilizing both primary and secondary sources. Primary data sources consist of in-depth interviews, focus group discussions, site visits, and document analyses extracted from the reports. Secondary sources encompass past literature relevant to the case study approach. The analysis identifies three key roles of academicians as solution providers: socioeconomic assurance, project sustainability, and the preservation of local wisdom. These roles are further enhanced through the application of the Technical and Vocational Education and Training (TVET) framework. The findings contribute to the valuable discussion on consistency in terms of academicians’ performance-oriented, knowledge discretion vis-à-vis farming community, and ubiquitous local wisdom. Crucial recommendations are proposed for solution providers in academia and policy deliverables in the Eastern Region for future endeavors to minimize multidimensional poverty through the funding of social community projects.